2013
DOI: 10.1186/1939-8433-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of breeding lines with three pyramided resistance genes that confer broad-spectrum bacterial blight resistance and their molecular analysis in rice

Abstract: BackgroundThe development of resistant cultivars has been the most effective and economical strategy to control bacterial leaf blight (BB) disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo). Molecular markers have made it possible to identify and pyramid valuable genes of agronomic importance in resistance rice breeding. In this study, three resistance genes (Xa4 + xa5 + Xa21) were transferred from an indica donor (IRBB57), using a marker-assisted backcrossing (MAB) breeding strategy, into a BB-susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
158
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 33 publications
16
158
0
1
Order By: Relevance
“…It has also been observed that the reported amino acid change is consistent among all 27 different resistant rice varieties tested and nine susceptible ones belonging to the Aus-Boro group (Iyer and McCouch 2004). This gene is also used in many bacterial resistance gene pyramiding programs worldwide (Sundaram et al 2008;Kottapalli et al 2010;Suh et al 2013). Recessive resistance genes are preferable, as those genes provide resistance to different pathogenic races with mechanisms of action different from those of the dominant resistance genes.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…It has also been observed that the reported amino acid change is consistent among all 27 different resistant rice varieties tested and nine susceptible ones belonging to the Aus-Boro group (Iyer and McCouch 2004). This gene is also used in many bacterial resistance gene pyramiding programs worldwide (Sundaram et al 2008;Kottapalli et al 2010;Suh et al 2013). Recessive resistance genes are preferable, as those genes provide resistance to different pathogenic races with mechanisms of action different from those of the dominant resistance genes.…”
Section: Introductionmentioning
confidence: 76%
“…oryzae (Xoo) limits rice production up to 81 % (Kumar et al 2012). Thirty-eight different resistance genes have been identified to combat this serious disease of rice (Suh et al 2013). Among them, xa5 is one of the major recessive resistance genes that provide a high degree of resistance to a wide range of Xoo races (Suh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different rice lines and varieties were taken for the study (Table 1) where the variety IRBB21 and BR-11 were considered as the resistant and susceptible cultivars for check [13][14][15] respectively. …”
Section: Methodsmentioning
confidence: 99%
“…However, because of rapid changes in pathogen virulence or population biotype, the qualitative resistance is not durable (Suh et al 2013). One strategy for breeding cultivars with durable and broad-spectrum resistance is pyramiding resistance loci.…”
mentioning
confidence: 99%